Phenotypic and genotypic characterization of alertpathogens isolated in the hospital environment - Mrowiec, Paulina (2012)
The aim of the PhD thesis was to determine the prevalence of alert pathogens among patients hospitalized between October 2008 and February 2010 in different departments of the Rydygier’s Hospital in Krakow. Moreover, the phenotypic methods (disk diffusion, Etest, the automatic system VITEK2 Compact) and genetic methods (PCR,multiplex-PCR, RT-PCR and RAPD-PCR) were applied in order to determine susceptibility patterns, the occurrence of resistance mechanisms and the genetic relatedness in the selected group of alert pathogens. Three hundred and eighty-one alert bacterial pathogens were tested including: Gram-negativerods, represented by multidrug-resistant nonfermenting strains of A. baumannii (105) and P.aeruginosa (46); strains of the Enterobacteriaceae family: K. pneumoniae (96), E. coli (38), E. cloacae(11), producing extended-spectrum betalactamases; and Gram-positive cocci represented by methicillin-resistant S. aureus (85).The monitoring of the susceptibility to antibacterial agents used in the clinical practice is necessary due to the rapid spread of the bacterial resistance mechanisms. The current epidemiological data as well as knowledge of resistance patterns of alert pathogens can provide useful information, which can be used to select the most effective treatment to avoid further rising of the resistance among microorganisms inhabiting the hospital environment.
Keywords: alert pathogens; PCR; molecular typing; resistance; nosocomial infections